The role of school climate on student disclosure of private information and cyberbullying: a comparison of regular and vocational school students in China - Chen, Qiqi; Tang, Jiaqi; Zhu, Yuhong; Chan, Ko Ling (Frontiers in Public Health, 2024)
Adolescents are experiencing an unprecedented cyber-saturated environment where the disclosure of private information should be approached with caution. This study aims to investigate the effects of school environment, including student support, teacher support, and opportunities for autonomy, on students’ disclosure of private information and their experiences with cyberbullying. In September 2022, a total of 1,716 students (mean age = 14.60, SD = 1.35) from three regular and vocational schools in China participated in the survey. The results showed that 35.6% of the participants had experienced victimization by cyberbullying, and 12.6% had perpetrated cyberbullying. Vocational school students reported significantly higher rates of cyberbullying and lower levels of perceived school climate than students from regular school. Student support in the school environment was found to negatively affect both cyberbullying perpetration and victimization, with this impact appearing to be stronger in regular schools as compared to vocational schools. Opportunities for autonomy and the disclosure of private information were positively correlated with experiences of cyberbullying. This study introduces a novel perspective that perceived school climate influences adolescents’ disclosure of private information and their involvement in cyberbullying. The findings could provide implications for future research and practices aimed at child protection in cyberspace.